The moderating effect of lifetime physical activity on brain alterations related to adverse childhood experiences - Zehirlioğlu, Lemye; Demirakça, Traute; Nkrumah, Richard O.; Ettingshausen, Lennart; Grauduszus, Yasmin; Schröder, Claudius von; Feichtmair, Melissa; Kleindienst, Nikolaus; Ende, Gabriele; Schmahl, Christian (European psychiatry, 2025)
BackgroundAdverse childhood experiences (ACEs) can cause morphological brain alterations across the lifespan, contributing to increased vulnerability to mental and physical disorders. Despite extensive research on ACEs-related brain alterations, the protective or augmenting role of modifiable lifestyle factors such as physical activity has been largely underexplored, representing a key gap in our understanding of trauma-related neuroplasticity. To close this gap, we aimed to investigate how lifetime physical activity (LPA) influences the relationship between ACEs and morphological brain alterations.MethodsModeration analyses using Hayes’ PROCESS macro examined the interaction between ACEs and LPA on the volume of limbic system-related regions - hippocampus, amygdala, anterior cingulate cortex (n = 81).ResultsWhile LPA showed no moderating effect on hippocampal or anterior cingulate volume, the model concerning the volume of the amygdala was significant. This model explained 8.1% of the variance in amygdala volume (p = 0.002) and the interaction of LPA and ACEs contributed 7.9% of this variance, with a significant effect (β = −0.221 p ≤ 0.001). That indicated LPA moderates ACEs-related structural changes in the amygdala, a key component of the central circuitry of emotion and stress sensitization. Notably, only in individuals with low physical activity were ACEs associated with increased volume of amygdala.ConclusionsOur findings underscore the behavioral dependency of the structural adaptations of the amygdala following childhood adversities. These results emphasize the therapeutic potential of incorporating physical activity into interventions for trauma-exposed individuals, offering a behavioral approach to mitigating stress-related neurobiological changes.